Human Rights and Human Rights Education: Beyond the Conventional Approach - Al-Daraweesh, Fuad (In Factis Pax: Journal of Peace Education and Social Justice, 2013)
The last three decades have witnessed an intellectual conflict between two diametrically opposed schools of thought on human rights. The first school of thought concerns the universalism of human rights, and the second is based on cultural relativism. Universalists are committed to the view that, while the discourse of human rights originated in the West, a common set of human rights standards can, and should, apply across cultures. For Cultural Relativists, there is no universally moral doctrine, since morality is viewed as a relative social and historical phenomenon. As follows from the relativist approach, human rights are valid only in and for those cultures that established the discourse of rights. Relativism emphasizes that values of human rights are at odds with traditional intercultural beliefs. This paper is an attempt to go beyond the dichotomy inherent in the Universalist-Relativist debate. As a prerequisite, to move beyond the debate, it is essential to acknowledge the nature of the dichotomies in existence (universalism versus cultural relativism, Western vs. Non-Western). This study is an effort to translate one perspective into another and discover a common denominator for the variance in perspectives.